2020
DOI: 10.1177/0898010120911540
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Traditional Medicine: Application of a Traditional and Complementary Medicine System to Improve Opioid Use Treatment in Latinos

Abstract: Background: Initially considered a primarily rural, White issue, opioid use and overdose rates have risen faster for Latinos (52.5%) than for White, non-Hispanics (45.8%) from 2014 to 2016. With an estimated 45% to 65% of Latino immigrant families using Mexican traditional medicine (MTM) practices before seeking Western medical services, these practices could be used as a method to increase access to care and improve outcomes. Practice Model: Although not well known, MTM is founded on a defined set of theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…Such findings indicate the need for a broader, more inclusive vision of health care and its potential benefits. For example, thought has been given as to how Mexican traditional medicine can be utilized and integrated along with formal health care to address substance use among migrants in the United States (Sorrell, 2020). Along with this current study, this body of work suggests that incorporating medical pluralism into every day practice with migrant populations has the potential to decrease health disparities among migrant groups.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings indicate the need for a broader, more inclusive vision of health care and its potential benefits. For example, thought has been given as to how Mexican traditional medicine can be utilized and integrated along with formal health care to address substance use among migrants in the United States (Sorrell, 2020). Along with this current study, this body of work suggests that incorporating medical pluralism into every day practice with migrant populations has the potential to decrease health disparities among migrant groups.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional and complementary services, such as THs, can be more acceptable to some members of the Latine community because these culturally competent and sensitive approaches can improve health outcomes, decrease stigma, and address disparities in access to treatments. 48 Barriers to biomedical health care identified were high cost of services, distance to providers, lack of transportation, and limited hours of availability of services, all of which contribute to participants' frequent use of THs. 35 Another study found comparable results citing problems with communication, establishing financial eligibility, and extremely long waits for medical appointments.…”
Section: Resultsmentioning
confidence: 99%
“…THs could work alongside public health and medical professionals to educate them on cultural humility and cultural relevance, thereby perhaps engendering more trust in the biomedical/medical system as cited by one study highlighting this pairing as a beneficial partnership. 48 …”
Section: Discussionmentioning
confidence: 99%
“…First, our study results may not be generalizable to patients from different races and ethnicities given our study population reflected that of Baltimore's population which is 63% Black and 28% non-Hispanic White with people of all other races/ ethnicities making up 9%. 40 Second, there is the risk that participants may exhibit a type of social desirability bias where they may use biomedical terms because they think is expected of them but may still hold perspectives that differ. 41 This social desirability bias might be more significant for three of the participants who receive care from the study author conducting the interviews.…”
Section: Discussionmentioning
confidence: 99%